2000
DOI: 10.1080/00288330.2000.9516936
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope composition of modern bryozoan skeletal carbonate from the Otago Shelf, New Zealand

Abstract: The oxygen (δ 18 O) and carbon (δ 13 C) isotope ratios of 10 species of living Bryozoa collected from the Otago Shelf, New Zealand were analysed to assess the extent to which isotopic equilibrium (relative to inorganic equilibrium isotope fractionation) is attained during the precipitation of skeletal calcium carbonate. The data reveal that whereas eight species of Bryozoa synthesise skeletal carbonate in apparent oxygen isotope equilibrium with respect to environmental conditions, two species (Celleporina gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 55 publications
3
20
0
Order By: Relevance
“…Our observations on mineralogical differences between winter and summer bands not only corroborate the effect of seasonal changes of seawater temperature on bryozoan mineralogy (Lowenstam 1954;Crowley and Taylor 2000;Smith and Key 2004), but also show the rapidity with which ambient temperature impacts the biomineralization process. Differences in mineralogical composition within bryozoan skeletons, especially in bimineralic species where the highest levels of aragonite are usually associated with secondary calcification processes, are usually attributed to different ontogenetic stages (Carson 1978;Hayward and Ryland 1998).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our observations on mineralogical differences between winter and summer bands not only corroborate the effect of seasonal changes of seawater temperature on bryozoan mineralogy (Lowenstam 1954;Crowley and Taylor 2000;Smith and Key 2004), but also show the rapidity with which ambient temperature impacts the biomineralization process. Differences in mineralogical composition within bryozoan skeletons, especially in bimineralic species where the highest levels of aragonite are usually associated with secondary calcification processes, are usually attributed to different ontogenetic stages (Carson 1978;Hayward and Ryland 1998).…”
Section: Discussionsupporting
confidence: 79%
“…Despite bryozoans exerting control over their own biomineralization, their skeletons are subject to some degree of environmental modification (Lowenstam and Weiner 1989;Smith and Key 2004;Smith et al 2006;Taylor et al 2008). It has been suggested that modern temperate bryozoan skeletons are reasonable indicators of seawater chemistry, being largely unaffected by kinetic and metabolic factors (Lowenstam and Weiner 1989;Bone and James 1993;Crowley and Taylor 2000;Smith and Key 2004). Nevertheless, taxon-specific and ontogenetic factors must be borne in mind when using mineralogical variations within bryozoan colonies, within species, among growth forms and within families to infer environmental factors (Poluzzi and Sartori 1974;Smith et al 1998;Smith and Key 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Smaller zooids are present in summer than winter growth bands, corresponding to the 'size-temperature' rule (Atkinson 1994 ). Observations on mineralogical differences between winter and summer bands not only corroborate the effect of seasonal changes of seawater temperature on bryozoan mineralogy (Lowenstam 1954 ;Crowley and Taylor 2000 ;Smith and Key 2004 ), but also show the rapidity with which ambient temperature impacts the biomineralization process. An increase in aragonite and in calcite with higher Mg content characterizes those parts of the skeleton formed in the summer, as previously observed in other bimineralic bryozoan species (Poluzzi and Sartori 1973 ;Rucker and Carver 1969 ).…”
Section: Responses To Climate Changementioning
confidence: 52%
“…Nevertheless, taxon-specifi c and ontogenetic factors also contribute to mineralogical variations seen within colonies, within species, among colony-forms and within families (Poluzzi and Sartori 1974 ;Smith et al 1998 ;Smith and Key 2004 ). Isotopically, bryozoan skeletons are generally in equilibrium with seawater (Lowenstam and Weiner 1989 ;Bone and James 1993 ;Crowley and Taylor 2000 ;Smith and Key 2004 ), although in a few instances disequilibrium may result from kinetic effects or possibly symbiosis (Crowley and Taylor 2000 ).…”
Section: Constructional Bryozoa In the Mediterranean Seamentioning
confidence: 98%
“…Using an estimated range of −0.5 to +0.5‰ PDB for the δ 18 O composition of New Zealand sea water (Feary et al, 1991;Crowley and Taylor, 2000), and the measured values of bottom water temperatures at the box core sites (Table 4), it is possible to constrain pore fluid compositions associated with carbonate precipitation based on the equilibrium equations for calcite (Friedman and O'Neil, 1977), aragonite (Grossman and Ku, 1986) and dolomite (Fritz and Smith, 1970), as summarised in Fig. 12 (Table 4) shows that our calcite samples range from slightly depleted to slightly enriched with respect to regional sea water (Fig.…”
Section: Oxygen Sources Of Hikurangi Margin Mdacsmentioning
confidence: 99%